Numerical Simulation and Backscattering Characteristics of Freak Waves Based on JONSWAP Spectrum - Wu, Gengkun; Han, Lichen; Zhang, Lihong (Frontiers in Marine Science, 2022)
Based on the linear wave superposition model, we realize the numerical simulation of three-dimensional (3-D) surface wave combined with JONSWAP spectrum and stereo wave observation project (SWOP) directional function. According to the formation characteristics of freak waves to concentrate the wave energy at a specific location, the component waves are modulated. A complete numerical simulation model of time-invariant 3-D freak waves evolution is first proposed in this study. Then, the accuracy of the model is verified from the aspects of wave height distribution, frequency spectrum estimation and freak wave parameters. The effectiveness of wave steepness as the discrimination condition of freak waves is discussed through experiments. In terms of the electromagnetic scattering characteristics of freak waves, we construct an electromagnetic scattering model, fitting the time-invariant 3-D freak wave, based on the two-scale method (TSM). By comparing and analysing the scattering characteristics D-value of synthetic aperture radar (SAR) image of the freak wave and the background wave, the rationality of the electromagnetic scattering characteristics of freak wave as its feature identification is verified. Comparing the normalized radar cross section (NRCS) of freak wave and background sea waves, the experiment shows that the NRCS value of freak wave is the lowest, and the calculation results of the two have obvious differences. The research conclusions above can provide effective data support for the identification and detection of freak wave in practical offshore engineering.